Peruphasma marmoratum, a remarkable new species of high montane Phasmatodea (Pseudophasmatidae: Pseudophasmatinae) from the Venezuelan Andes - Murányi, Dávid (Zootaxa, 2007)
A remarkable new species of high montane Phasmatodea (Pseudophasmatidae: Pseudophasmatinae), Peruphasma marmoratum sp. n. from the Venezuelan Andes is described and illustrated from both sexes. The species of Peruphasma Conle & Hennemann, 2002, which were excluded by Zompro (2004) are confirmed as belonging to the genus. The new species differs from all other members of the genus by the presence of tubercles on the mesonotum. Affinities, ecological and distributional notes, and notes on other Anisomorphini from Venezuela are presented.